The Efficacy and Safety of Switching From Originator Infliximab to Single or Double Switch Biosimilar Among a Nationwide Cohort of Inflammatory Bowel Disease Patients. Issue 2 (26th April 2021) - Khan, Nabeel; Patel, Dhruvan; Pernes, Tyler; Patel, Manthankumar; Trivedi, Chinmay; Medvedeva, Elina; Xie, Dawei; Yang, Yu-Xiao
Abstract: Background: Data on safety and efficacy of switching to Renflexis (SB2) from originator Infliximab (IFX) (single switch) or from originator IFX to Inflectra (CT-P13) to Renflexis (double switch) are limited. Methods: We conducted a retrospective cohort study in a nationwide cohort of patient with inflammatory bowel disease (IBD) in remission who were switched to SB2. The main exposure was the treatment course of SB2. There are 2 levels in this variable: single switch (IFX to SB2) and double switch (IFX to CT-P13 to SB2). The outcome is SB2 drug discontinuation rate and/or not being in remission after 1 year. Logistic regression was used to estimate the adjusted and unadjusted odds ratios with 95% confidence intervals to study the efficacy difference between single switch and double switch. Results: A total of 271 IBD patients were started on SB2. Among them 52 (19.2%) patients did not achieve remission at 1 year and 14 (5.1%) patients had to discontinue SB2 due to adverse events). In logistic regression analysis after controlling for covariates, there was no statistically significant difference observed in regard to efficacy or safety of the single switch versus double switch to SB2 (adjusted odds ratio for double switch compared to single switch = 1.33 (95% confidence interval 0.74–2.41, P = 0.3432). Conclusions: Among IBD patients in remission, double switch was equally effective as compared to a single switch. This will help reassure the gastroenterologists who have concerns regarding the safety and efficacy of switching between multiple biosimilars for treating IBD. Lay Summary: Almost 81% of patients remained in remission after switching to a biosimilar at the end of 1 year. A double switch was not associated with a worse outcome as compared to a single switch.